The impact of enhancing perceived self‐efficacy in torture survivors. Issue 1 (7th September 2017) - Morina, Naser; Bryant, Richard A.; Doolan, Emma L.; Martin‐Sölch, Chantal; Plichta, Michael M.; Pfaltz, Monique C.; Schnyder, Ulrich; Schick, Matthis; Nickerson, Angela
Abstract : Background: Perceived self‐efficacy (SE) is an important factor underlying psychological well‐being. Refugees suffer many experiences that can compromise SE. This study tested the impact of enhancing perceived SE on coping with trauma reminders and distress tolerance in tortured refugees. Methods: Torture survivors ( N = 40) were administered a positive SE induction in which they retrieved mastery‐related autobiographical memories, or a non‐SE (NSE) induction, and then viewed trauma‐related images. Participants rated their distress following presentation of each image. Participants then completed a frustration‐inducing mirror‐tracing task to index distress tolerance. Results: Participants in the SE condition reported less distress and negative affect, and improved coping in relation to viewing the trauma‐related images than those in the NSE condition. The SE induction also led to greater persistence with the mirror‐tracing task than the NSE induction. Conclusions: These findings provide initial evidence that promoting SE in tortured refugees can assist with managing distress from trauma reminders, and promoting greater distress tolerance. Enhancing perceived SE in tortured refugees may increase their capacity to tolerate distress during therapy, and may be a useful means to improve treatment response.